Opening remarks by Prof. Tjama Tjivikua, Vice Chancellor, NUST, on the occasion of the 2nd EOSA-RTC symposium titled "Towards a vision for space science, technology and applications in Namibia", 24 July 2013, Windhoek. - Tjivikua, Tjama (My University, 2013)
Earth Observation and Satellite Applications Research and Training Centre
EOSA-RTC symposium (2013 Jul. 24 : Windhoek)
Keywords: EOSA-RTC Symposium (2013 Jul. 24 : Windhoek); Earth Observation and Satellite Applications Research and Training Centre - Symposium; Space science - Namibia; Speeches, addresses, etc.